新山中华公会的族群系统研究 = The ethnic system of Persekutuan Tiong-Hua, Johor Baru - 林鼎瀚 Lim, Ding Han (2014)
华人社团向来是海外华人研究中的一大课题，地缘、血缘及业缘组织更是学界经常探讨的对象。本文试图以另一类的综合性组织——新山中华公会为研究对象，欲窥其与族群系统的互动关系。本文使用了新山著名的地方学者安焕然所提出的“公系统”理论来探讨公会如何在华人社会的公共领域运作，并且如何代表华社来与政府或政党进行互动。首先厘清新山中华公会的历史背景，得知其组织性质与领导格局有着历史的渊源，乃从私会党柔佛义兴公司转型而成，进而验证公会的领导地位及探讨其领导地位的转变，以期了解公会是否有效地整合新山华社。新山中华公会既为新山华社的最高领导机构，自然离不开与政治进行互动，而它受到了来自大环境及小环境的影响。公会在国际冷战大环境的影响下，其内部产生了左派及右派的斗争；而另一方面，在马来西亚国内政局的影响下，有着执政党“基因”的公会领导层长期采取“协商模式”，偏靠执政党，使得公会成为一个不“公”的组织。 “公系统”是华人民间社会与权力机构进行角力、对话、冲突、协商的一大场域，而它所强调的是包容性，即包容各种声音，但是由于公会的不“公”，使得公会在“公系统”里的公信力受到打击。Chinese organisations have always been a major topic of interest, whilst geographical, consanguineal and occupational organisations have always been main perspectives of academic discussion in the studies of ethnic Chinese. This thesis will attempt to investigate the relationship between Persekutuan Tiong-Hua, Johor Baru, a multi-faceted organisation and ethnic system via the following areas. This thesis will employ the theory of “public cultural system” proposed by renowned Johor Bahru scholar An Huanran when discussing about the operations of Persekutuan Tiong-Hua, Johor Baru in the public space of the Chinese society and masses along with how it represents the Chinese society in engagement with the ruling party. Firstly, a historical survey of Persekutuan Tiong-Hua, Johor Baru reveals that the nature of its organisation and leadership structure has its historical roots founded upon the triad, Ngee Heng Kongsi of Johor. The evolution of the leadership role of Persekutuan Tiong-Hua, Johor Baru will thus be discussed together with the substantiation of its actual leadership role as a leading Chinese organisation, allowing us to understand whether Persekutuan Tiong-Hua, Johor Baru has effectively merged the Chinese society of Johor Bahru into conformity. Persekutuan Tiong-Hua, Johor Baru, the leading Chinese organisation of the Chinese society of Johor Bahru naturally sees political interactions, and is influenced by both the macro and micro environment it is subjected to. Persekutuan Tiong-Hua, Johor Baru saw a struggle within the leftists and rightist sects within under the influence of an international Cold War. However, the influence of Malaysian domestic politics saw Persekutuan Tiong-Hua, Johor Baru which has the “genes” of the ruling party adopting a liberal approach, adjusting its political stance in favor of the ruling party, casting doubts of its “public” nature. “Public cultural system” is the vast public space where the Chinese society and masses engages in struggles, dialogue, conflicts and compromise with the jurisdictional agency. The “public cultural system” emphasises on inclusion, an inclusion of different voices, but Persekutuan Tiong-Hua, Johor Baru’s drift from its “public” nature essentially causes doubts on its credibility in the “public cultural system”.